Nursing care provided to persons deprived of liberty in the hospital environment - Polyanna Bezerra Alves da Silva; Mayara Lima Barbosa; Lannuzya Veríssimo e Oliveira; Gabriela Maria Cavalcanti Costa
ABSTRACT Objectives: To describe the nursing care provided to people deprived of liberty (PDL) in the hospital environment. Methods: An exploratory-descriptive study with a qualitative approach, conducted with 38 nursing professionals in three regional hospitals located in the Northeast of Brazil, between March and July of 2016. Content analysis was performed on the data. Results: Two categories emerged from the analysis: nursing care provided to people deprived of liberty in the hospital setting and self-evaluation of nursing care provided to PDL. Final considerations: The nursing care delivered to people deprived of liberty in the hospital environment is limited to technical procedures, revealing a fragmented work process that falls short of the standards of public policies. We found that structural deficiency, particularly regarding safety in the hospital environment, associated with lack of professional training to deal with this clientele, make nursing care difficult in this context.